METHODS OF DEVELOPING HEARING-SPEAKING SKILLS: METHODS OF DEVELOPING HEARING-SPEAKING SKILLS - Космуратов, Алтынбек; Тукмирзаева, Айгерим (Журнал иностранных языков и лингвистики, 2025)
Before proceeding to outline the methodology of grammatical and lexical skill formation, it is necessary to consider two general issues concerning the work at this stage. The formation of a skill with all its inherent qualities, especially automaticity, stability, flexibility and relative complexity, requires certain conditions. Since conditions are created in exercises, it becomes clear that special exercises are necessary for the formation of speech skills. These exercises must meet certain requirements derived from the principles of the communicative method.